Pengembangan Media Pembelajaran Fisika Berbantuan 3D Application Scratch Pada Topik Getaran Dan Gelombang Untuk Meningkatkan Hasil Belajar Peserta Didik - Alifathoriq Yogamas Wakidawantama; Riki Perdana (Program Studi Pendidikan Fisika Universitas Katolik Widya Mandira, 2024)
Physics is often considered a less desirable subject due to the complexity of the learning faced by students. The use of physics learning media is very important in the teaching process to attract students' interest. The use of 3D Scratch applications can help in making learning media, such as vibration and wave simulations using balls. By utilizing Scratch, physics material that is abstract can be explained more easily and interestingly for students. This research focuses on the development of scratch-based physics learning media, especially on the topic of vibrations and waves, with the aim of improving student learning outcomes. The research method used is the 4D development model, involving the defining, planning, developing, and disseminating stages. Evaluation was conducted using the SBi method by converting ordinal data to intervals using MSi analysis. The results showed that the learning media created can be categorized as feasible. Thus, this learning medium can be effectively used in physics learning activities, helping students understand the concepts of vibration and waves.